Perioperative/postoperative anxiety and its interventions in gynecological cancers: a comprehensive review of clinical evidence - Chen, Beibei; Chen, Chunyan; Zhao, Xiumin; Xia, Dongyue (Frontiers in Psychiatry, 2024)
Gynecological cancers are the common malignancies in females, with surgical intervention being the main therapeutic modality that presents the potential for a definitive cure. Mounting research has identified that gynecological cancer patients are vulnerable to anxious symptom during the perioperative and postoperative period, while this psychological disorder has been found to be associated with poor recovery after a surgical procedure. However, some interventions have also been found to alleviate perioperative and postoperative anxiety for gynecological cancers patients.Gynecological cancers are prevalent malignancies among females, and surgical intervention is the primary therapeutic approach offering the possibility of a definitive cure. Recent research has highlighted the susceptibility of gynecological cancer patients to experiencing anxiety symptoms during the perioperative and postoperative phases, with this psychological condition being linked to suboptimal recovery following surgery. Nevertheless, certain interventions have shown promise in mitigating perioperative and postoperative anxiety in gynecological cancer patients. We conducted a comprehensive review to collect the existing evidence on this subject. Through a systematic search across six common databases, we screened and included 28 pertinent studies. The current review emphasizes the elevated occurrence of perioperative and postoperative anxiety among patients with gynecologic and gynecologic cancers (i.e., uterine, cervical, ovarian, endometrial, and vulval cancers). Specific nursing interventions (i.e., crisis intervention nursing, multidisciplinary collaborative continuous nursing, psychological nursing, comprehensive psychological nursing, reminiscence therapy involved care, cognitive behavioral stress management, hospital-family integrated continuation nursing, high-quality nursing care, relaxation-focused nursing program, and relaxation/counselling counseling intervention) and psychotropic medications may serve as dependable approaches for mitigating perioperative and postoperative anxiety. To our knowledge, this study is the first to characterize perioperative/postoperative gynecological oncology-associated anxiety. This review highlights that perioperative and postoperative anxiety is a non-negligible clinical issue for patients with gynecologic and gynecologic cancers, which should be established in intervention studies. This study represents a novel contribution to the literature by providing a characterization of perioperative and postoperative anxiety in the context of gynecological oncology. The findings underscore the significance of addressing perioperative and postoperative anxiety as a critical clinical concern for individuals with gynecologic and gynecologic cancers, emphasizing the need for further research to develop effective interventions.